Development and assessment of a Mentor Training Workshop Series and Certificate Program - Kenzie A. Cameron; Mercedes R. Carnethon; Morgan Barrowman; Leah J. Welty (Journal of Clinical and Translational Science)
Within the Northwestern University Clinical and Translational Sciences Institute, we created a foundational and fluid mentor training curriculum to provide competency-based mentor training for faculty. Via our “Developing and Enhancing Mentoring Relationships” mentor workshop series, launched in 2020, we present eight 90-minute workshops each academic year. This series is designed for both training naive participants and previously trained mentors across ranks and tracks and offers both repeating (“required”) and new (“elective”) workshops annually. We implemented a Mentor Training Certificate Program (MTCP) in 2021 to formally recognize faculty who complete a minimum of nine hours of training, consisting of three required and at least three elective training sessions. Over the first four years of the workshop series, 345 unique faculty attended at least one workshop; 46 completed requirements for the MTCP. MTCP participants complete baseline and annual surveys focused on self-assessment of nine mentoring skills (e.g., providing feedback) and frequency of engaging in five recommended mentoring behaviors (e.g., aligning expectations). Scores increased significantly across all skills; participants reported increased frequency of mentoring behaviors and high satisfaction with the program. Our mentor workshop series, offering both repeating and new workshops annually, provides faculty the opportunity for either initial or advanced training.